2015
DOI: 10.1016/j.nmni.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Butyricimonas virosa: the first clinical case of bacteraemia

Abstract: The strictly anaerobic Gram-negative bacteria Butyricimonas species have recently been described in human faeces and have to our knowledge not been isolated in infectious clinical materials. We report the first case of Butyricimonas virosa bacteraemia in a 72-year-old man with colon adenocarcinoma, who underwent aortic aneurysm replacement surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 6 publications
(4 reference statements)
2
28
0
Order By: Relevance
“…Consistent with the report of Ulger Toprak et al. [1] , our isolate grew anaerobically on Brucella blood agar (Becton Dickinson, Franklin Lakes, NJ, USA), and on Gram stain appeared as a small Gram-negative rod. Our isolate was catalase positive and was resistant to kanamycin (1 mg), vancomycin (5 μg) and colistin sulfate (10 μg).…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the report of Ulger Toprak et al. [1] , our isolate grew anaerobically on Brucella blood agar (Becton Dickinson, Franklin Lakes, NJ, USA), and on Gram stain appeared as a small Gram-negative rod. Our isolate was catalase positive and was resistant to kanamycin (1 mg), vancomycin (5 μg) and colistin sulfate (10 μg).…”
supporting
confidence: 91%
“…We read with interest the recent report by Ulger Toprak et al. [1] reporting the first case of Butyricimonas virosa bacteraemia published earlier this year. Here we describe the case of a 72-year-old man with colon cancer who presented with septic shock after aortic aneurysm surgery, with Butyricimonas virosa recovered from blood cultures.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Ethanol-induced liver injury increased the relative abundance of Butyricimonas spp., which positively correlated with the levels of liver injury parameters such as AST and ALT (36). The species B. virosa has been reported to be associated with bacteremia (37)(38)(39). We also found that Oscillibacter spp.…”
Section: Discussionsupporting
confidence: 57%
“…The family Porphyromonadaceae contains 11 genera: Porphyromonas (type genus) , Barnesiella, Butyricimonas, Dysgonomonas, Macellibacteroides, Odoribacter, Paludibacter, Parabacteroides, Petrimonas, Proteiniphilum and Tannerella [12] . Butyricimonas virosa bacteraemia has been described in patients with colon cancer [13] , [14] and in patients with posttraumatic chronic bone and joint infection [14] .…”
Section: Introductionmentioning
confidence: 99%